Delivering TfL's Investment Programme: A Knowledge Integration Ethos for Middle Managers - Mensah, Emmanuel Edmondson (2006)
London transport system has suffered for decades from a lack of consistent investment. Government Ministers have always acknowledged that effective transport in the Capital is vital for the prosperity of the United Kingdom and the wellbeing of London, and yet governments have historically under-funded a system that was once the envy of the world and inspired imitators around the globe. Even when funding was pledged, all too often the amount was chopped and changed year after year. The result being a seriously rundown infrastructure and insufficient capacity to meet London TfL an all too familiar reality to the 10 million passengers who use the public transport network every day. Now however, a groundbreaking settlement with Government has provided a once-in-a-generation opportunity for London to reverse this decline. Transport for London (TfL) has the certainty of being able to invest ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂ ÃÂ¢Ã¢ÂÂ¬Ã¢ÂÂ¢ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂ¢Ã¢ÂÂÃÂ¢ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂÃÂÃÂÃÂ¢ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃ¢ÂÂÃÂÃÂ¬ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¦ÃÂÃ¢ÂÂÃÂÃÂ¡ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂ ÃÂ¢Ã¢ÂÂ¬Ã¢ÂÂ¢ÃÂÃÂÃÂÃÂ¢ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃÂ¬ÃÂÃ¢ÂÂ¦ÃÂÃÂ¡ÃÂÃÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃ¢ÂÂÃÂÃÂ£10 billion in London transport over the next five years. There is ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂ ÃÂ¢Ã¢ÂÂ¬Ã¢ÂÂ¢ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂ¢Ã¢ÂÂÃÂ¢ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂÃÂÃÂÃÂ¢ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃ¢ÂÂÃÂÃÂ¬ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¦ÃÂÃ¢ÂÂÃÂÃÂ¡ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂ ÃÂ¢Ã¢ÂÂ¬Ã¢ÂÂ¢ÃÂÃÂÃÂÃÂ¢ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃÂ¬ÃÂÃ¢ÂÂ¦ÃÂÃÂ¡ÃÂÃÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃ¢ÂÂÃÂÃÂ£3 billion in new borrowing on top of ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂ ÃÂ¢Ã¢ÂÂ¬Ã¢ÂÂ¢ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂ¢Ã¢ÂÂÃÂ¢ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂÃÂÃÂÃÂ¢ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃ¢ÂÂÃÂÃÂ¬ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¦ÃÂÃ¢ÂÂÃÂÃÂ¡ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂ ÃÂ¢Ã¢ÂÂ¬Ã¢ÂÂ¢ÃÂÃÂÃÂÃÂ¢ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃÂ¬ÃÂÃ¢ÂÂ¦ÃÂÃÂ¡ÃÂÃÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃ¢ÂÂÃÂÃÂ£4 billion scheduled to be invested through existing Public Private Partnerships (PPP) and Private Finance Initiative (PFI) contracts. In addition to this there is also ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂ ÃÂ¢Ã¢ÂÂ¬Ã¢ÂÂ¢ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂ¢Ã¢ÂÂÃÂ¢ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂÃÂÃÂÃÂ¢ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃ¢ÂÂÃÂÃÂ¬ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¦ÃÂÃ¢ÂÂÃÂÃÂ¡ÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂ ÃÂ¢Ã¢ÂÂ¬Ã¢ÂÂ¢ÃÂÃÂÃÂÃÂ¢ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃÂ¬ÃÂÃ¢ÂÂ¦ÃÂÃÂ¡ÃÂÃÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃ¢ÂÂÃÂÃÂ£3 billion of capital investment funded from Government grant. The question now is how London TfL delivers on the promises made in securing the funding from government to develop the Transport Infrastructure. This dissertation focuses on the middle managers within Surface Transport, ie, all transport modes apart from London Underground, with direct responsibility for delivering the projects enshrined in the investment programme, and how that delivery can be enhanced by integrating knowledge and experiences gained in the delivery of projects across all transport modes. 40 middle managers across a majority of the Surface Transport modes were interviewed with the view to identifying the salient issues and establishing a framework for an organization paradigm shift from silo driven mentalities toward a new ethos of sharing and integrating knowledge across the disparate modes. The findings from the interviews are presented in two segments. The first is an identification of the awareness of the investment programme and its key deliverables, and the second advances the key issues hampering knowledge integration with Surface Transport and how it can be overcome. To this end, this dissertation makes a number of contributions which, when implemented, would greatly enhance the sharing and integration of knowledge across all Surface Transport modes vis-a-vis the very crucial issue of delivering the projects in the 5 year investment programme. (2005)